Chromium deposition and poisoning of La0.8Sr0.2MnO3 oxygen electrodes of solid oxide electrolysis cells. (24th July 2015) - Chen, Kongfa; Hyodo, Junji; Dodd, Aaron; Ai, Na; Ishihara, Tatsumi; Jian, Li; Jiang, San Ping
Abstract : The effect of the presence of an Fe–Cr alloy metallic interconnect on the performance and stability of La0.8 Sr0.2 MnO3 (LSM) oxygen electrodes is studied for the first time under solid oxide electrolysis cell (SOEC) operating conditions at 800 °C. The presence of the Fe–Cr interconnect accelerates the degradation and delamination processes of the LSM oxygen electrodes. The disintegration of LSM particles and the formation of nanoparticles at the electrode/electrolyte interface are much faster as compared to that in the absence of the interconnect. Cr deposition occurs in the bulk of the LSM oxygen electrode with a high intensity on the YSZ electrolyte surface and on the LSM electrode inner surface close to the electrode/electrolyte interface. SIMS, GI-XRD, EDS and XPS analyses clearly identify the deposition and formation of chromium oxides and strontium chromate on both the electrolyte surface and electrode inner surface. The anodic polarization promotes the surface segregation of SrO and depresses the generation of manganese species such as Mn 2+ . This is evidently supported by the observation of the deposition of SrCrO4, rather than (Cr, Mn)3 O4 spinels as in the case under the operating conditions of solid oxide fuel cells. The present results demonstrate that the Cr deposition is essentially a chemical process, initiated by the nucleation and grain growth reaction between the gaseous Cr species and segregated SrO on LSM oxygen electrodes under SOEC operating conditions.